﻿The effect of 1.3 bis(p-Hydroxyphenyl)urea compound on IL-6, IL-1β, TNF-α and COX-2 protein expression on λ-Carrageenan-induced rats - Denny Satria; Syukur Berkat Waruwu; Yuandani Yuandani; Hari Purnomo; Urip Harahap (Pensoft Publishers, 2022)
Objectives: This study aims to determine the protein expression of IL-6, IL-1β, TNF-α, and COX-2 using an immunohistochemistry method based on the anti-inflammatory activity of intraplantar carrageenan solution in male rat paws. Materials and methods: Animals were provided with 1.3 bis(p-Hydroxyphenyl)urea at 12.5, 25, 50, 100, and 200 mg/kg BW. This was administered approximately one hour before the 1% carrageenan induction. As a control measure, diclofenac sodium and CMC sodium 0.5% was similarly administered. After 360 mins, all of the rats were sacrificed, and the inflammatory tissue in the rat's paw was acquired. The immunohistochemistry preparations were carried out to observe the expression of IL-6, IL-1β, TNF-α, and COX-2. Results: The result showed a decrease in the expression of IL-6, IL-1β, TNF-α, and COX-2, all groups given 1.3 bis(p-Hydroxyphenyl)urea and diclofenac sodium compared to the control group CMC sodium 0.5% CMC sodium 0.5%. From the results of the mean difference test, it can be seen that the IL-1β expression at doses of 50, 100, and 200 mg/Kg BW was not significantly different from that of diclofenac sodium (p > 0.05). Meanwhile, the expression of COX-2, TNF-α, and IL-6 at doses of 100 and 200 mg/Kg BW was not significantly different from that of diclofenac sodium (p > 0.05). Conclusion: The 1.3 bis(p-Hydroxyphenyl)urea has anti-inflammatory activity by decreasing the percentage of IL-6, IL-1β, TNF-α, and COX-2 protein expression in rat's paw inflammation tissue.